Deskripsi Budaya Organisasi dalam Amal Usaha Muhammadiyah (Studi Kasus Universitas Muhammadiyah Gorontalo) - Muh. Firyal Akbar; Sri Handyani Suprapto; Widya Kurniati Mohi (Universitas Muhammadiyah Ponorogo, 2019)
This research is generally aimed at strengthening Muhammadiyah union institution in one of Muhammadiyah's business charity in Gorontalo Province, whereas specifically the purpose of this research is to know objective description about reality that happened at campus of Muhammadiyah University of Gorontalo from organizational culture that developed on campus This, taking into account the organizational culture found in Muhammadiyah in accordance with the PHIWM. This research uses qualitative method with case study approach. Data collection techniques used are observation, interview and documentation. Research time started from January to June 2017 From the results show that the employees have not implemented properly. Indicators of hard work still have not shown good results because most employees still do not understand the main duties and functions in work. Discipline indicators are also not well implemented where there are still many employees who enter the campus through the provisions of the time set as well while attending events on campus and when entering the time of prayer still not heed these things. The last indicator is the optimization in the work also has not shown the maximum results because only a few who are able to work effectively in accordance with the work agenda that they set previously.